Personal Deictic Expression in The Quran: A Pragmatic Study on The English Interpretation of Surah Al-Baqarah - Muhassin, Mohammad; Pradana, Satria Adi; Hidayati, Dewi Ayu (English Education: Jurnal Tadris Bahasa Inggris, 2020)
This study aims to find out and describe the pronouns used as personal deictic expressions in the Quran, the function, and the use of personal deictic expression. This is a kind of descriptive qualitative research.  The data are verses of Surah Al-Baqarah containing personal deictic expression chosen by purposive sampling technique. The researcher used a documentation method and  a note-taking  technique  in collecting the data. The result of the research shows that there 22 pronouns used as personal deictic expression in the Quran. They include I, We, You, They, He, She, It,My, Our, Your, Their, His, Her, Its, Me, Us, Them, Him, Yourselves, Themselves, Himself, Herself. Moreover, the function of personal deictic expression covers Subject, Object, Object of preposition, and Possessive. Meanwhile, the personal deictic expressions are used anaphorically, deictically, and cataphorically.